Democracy and Social Citizenship: A View from Liberalism (and its Disconforts…) (Andamios, Revista de Investigación Social, 2025)
The liberal tradition emphasizes the exercise of a set of rights linked to certain freedoms to the detriment of the social and economic rights of citizenship. The emergence of neoliberalism at the end of the 20th century consolidated an approach to social risk whose consequences are forceful: precarious citizens living in representative democracies but showing discomfort and distrust in the face of them, undermining their legitimacy as a form of government. This article suggests that modern societies that call themselves democratic have strong contradictions between the formal recognition of citizens’ rights and their ability to be exercised. This condition promotes political disaffection, which forces us to rethink liberalism from an egalitarian approach as a possibility of the reconfiguration of the political.
Keywords: Democracy; citizenship; rights; liberalism; State